PELAKSANAAN METODE KOOPERATIF TIPE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) PADA PEMBELAJARAN PAI SISWA KELAS X DALAM MENINGKATKAN KUALITAS HASIL BELAJAR MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMAN 1 TAMBUN UTARA - Azzam Kautsar; Yayat Suharyat (Universitas Maritim AMNI Semarang, 2022)
The purpose of this study is to overcome the problem of learning that is not optimal in class XI students of SMA 1 Tambun Utara, and the lack of attractiveness in PAI lessons because the method used is too monotonous so that it makes students feel bored quickly, there are problems in the use of learning media that make student learning outcomes not good. In the case of SMA 1 Tambun Utara, the delivery of material by the teacher in the learning media uses the lecture method, where the teacher is more active in speaking and students tend to be silent to listen, thus making students unable to master the material well. To overcome it all, researchers suggest using new media such as demonstrations, as a way to increase students' interest in learning. The Demonstration Method is a medium that has elements of demonstration. This study is intended to answer the problem